A non-destructive testing methodology for damage assessment of reinforced concrete buildings after seismic events. (15th May 2018) - Polimeno, Maria Rita; Roselli, Ivan; Luprano, Vincenza A.M.; Mongelli, Marialuisa; Tatì, Angelo; De Canio, Gerardo
Highlights: A new procedure for on-the-field inspection of RC buildings by NDTs was formulated. It was experimented on a full-scale RC mock-up subjected to shaking table tests. High correlation between RID and ultrasonic velocity reduction at columns was found. Sonic tests allowed rapid assessment of global state of damage of RC mock-up. Virtual mapping of column sections damage by ultrasonic tomography was experimented. Abstract: In the present study non-destructive testing (NDT) methods involving ultrasonic and sonic wave propagation in the solid matter were applied in order to detect and investigate the modifications induced by the seismic load on reinforced concrete (RC) buildings. In particular, the aim of this experimental work was to delineate a methodology for quick and easy application on-the-field to provide information on the state of health of a RC structure subjected to a seismic event by investigating the columns in lower stories, which are generally more safely reachable for inspection. The methodology was experimented through shaking table tests reproducing several earthquakes. Shaking table tests were performed at ENEA Casaccia Research Centre on a full-scale 2-storey RC frame building designed under the current Italian code (NTC2008). Among the considered NDT techniques, direct and indirect sonic methods, as well as partial and complete approaches for ultrasonic tomography application were explored. The above NDTs were applied to the specimen before and after the shaking table testing. Numerical simulations by finite element methods (FEMs) were also adopted for a better comprehension of the dynamic behaviour of the specimen and interpretation of the experimental results. Through the comparison with typical damage indicators formulated for RC buildings, derived from the modal parameters evolution and from the displacements of the structure during the seismic load, promising indications were obtained and the proposed NDT-based methodology was discussed.